We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
113
1
avatar

http://prntscr.com/m862gs

 Jan 16, 2019
 #1
avatar+102372 
+2

f(2)  =  12

 

The inverse to f  =    (x / 3)^(1/2)  = f -1

 

The derivative of this is    (1/3)(1/2)(x/3)^(-1/2)  = (1/6)(x /3)^(-1/2)

 

So   

 

df-1 / dx     at     f(2)   =  12   is

 

(1/6) (12/3)^(-1/2)  =

 

(1/6) ( 4)^(-1/2)  =

 

(1/6) / √4 =

 

(1 ) / ( 6 * 2)  =

 

1 /12

 

 

cool cool cool

 Jan 17, 2019

8 Online Users